Basic concept of inductance for inductive transducers - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
Inductance is a property exhibited by a circuit element, called inductor. This property is a result of a changing magnetic field associated with a coil of given number of turns wounded on air core or core of some materials. Accordingly inductance depends on the geometrical dimensions, and the turns and the core used. Invariably the most important cause for a magnetic field is the current flowing through the turns. If current is varying with time, the magnetic field is varying with time. A time-varying magnetic field includes a voltage in any conductor linked by the field, and as a result the coil causes a drop in the voltage applied. The circuit parameter of inductance displays a dormant behavior for a continuous current flow. The coil breaks its non-dormant behavior open when the current flow experiences a change